Tense relationship between General Didactics and Didactics of the disciplines (Praxis Educativa, 2012)
Didactics as a scientific discipline is a questioned knowledge nowadays. We start from the hypothesis of a double Historical loss that has mutilated the Didactics: The negation of its history which lost its socio-political roots and its links with the compromise to make a better society able to fight for universal peace, in the sense that Comenio gave to it in the XVII century. Losing its political frame it is limited to the coordinates of a didactic triangle in the reduced space of the classroom. The second historical loss for argentine Didactics was the abandonment of teaching investigation that had started with V. Mercante in the UNLP. In the meanwhile, the influences of Piaget and his disciples’ research works entered the country and started to strengthen the Didactics of particular disciplines or areas that develop through investigation works and are multiplied in different tendencies. This intellectual movement doesn’t seem to be translated into learning improvements. To analyze the impact emerging From these currents we have designed simple dispositives to test some learning which had been previously selected as priorities by the State. In this article, we show some results of tests about fractional numbers in Tercer Ciclo EGB. They show us important difficulties in the learning process of a high percentage of students. The conclusions of this work allow us to state that the changes proposed from the Didactics should be done since situated investigation before generalizing teaching principles to the whole scholastic population. Besides, the fragmented knowledge about teaching requires a holistic conception of Didactics focused in teaching as a political practice that involves the present and future of new generations. Through investigation work it is possible to build theory which fit the culture of our times, especially in the development of autonomy and the potentiality of groups through cooperative, institutional and democratic systems of evaluation.
Keywords: didactics; special didactics; evaluation; induced mistakes; longitudinal investigation